Off-ramps and on-ramps : keeping talented women on the road to success - Hewlett, Sylvia Ann, 1946- (Harvard Business School Press, 2007)
Examines the impact that a leave to care for children or elderly parents has on the career of professional women and proposes strategies that companies can undertake to retain and reintegrate talented female employees.